Optimization of fermentation conditions for Bacillus velezensis TCS001 and evaluation of its growth promotion and disease prevention effects on strawberries - Hao Cao; Zhilei Chen; Xuesong Li; Gening Song; Yuntian Wu; Jing Jin; Feng Cui; Jing Yuan; Huan Qi; Jidong Wang; Jie Chen (Biological Control)
Bacillus velezensis TCS001 is a novel biocontrol bacterium with broad-spectrum antifungal activity and plant growth-promoting effects, holding great potential for development in agricultural production. This study optimized the fermentation conditions for B. velezensis TCS001 through single-factor experiments combined with response surface methodology, and developed a formulation for TCS001 suspension concentrate (TCS001-SC). The efficacy of TCS001-SC to promote the growth of strawberries and to prevent and control strawberry anthracnose was evaluated. The optimal liquid fermentation condition for TCS001 was determined to be 2.89 % soluble peanut cake powder, 3.0 % glucose, 3.0 % soluble starch, 0.002 % FePO4, 0.006 % KCl, 0.6 % NaCl, 0.05 % MgCl2·6H2O, 0.3 % K2HPO4, 0.15 % KH2PO4, 0.05 % CaCO3, 0.005 % MnSO4, a working volume of 31 % (77.5 mL/250 mL), a rotation speed of 173 r/min, a cultivation temperature of 28°C, an inoculum volume of 1.0 %, and a pH of 7.0. The 15 L fermenter upscale culture achieved a spore count of 9.46 × 109 CFU/mL, which was 2.01 times the spore count of 4.7 × 109 CFU/mL before optimization, and a preliminary TCS001-SC was developed with the fermented broth as the main component. Agar plate confrontation tests showed that TCS001 had antifungal activity against five types of anthracnose fungi, with inhibition rates ranging from 70.3 % to 87.2 %. TCS001-SC could promote the growth of strawberries and induce a rapid defense enzyme response in their leaves, enhancing the plant's resistance to pathogens. After treatment, individual strawberry plants showed significant increases in the number of leaves, fresh weight of stems and leaves, root fresh weight, leaf area, plant height, and the content of POD, SOD, CAT enzymes, GA, IAA, and ABA compared to the control.Additionally, it shows good prevention and control effects against strawberry anthracnose, with a control efficacy of 60.45% after five spray treatments at a concentration of 2 × 107 CFU/mL, which is not significantly different from the efficacy of commercial microbial agents such as Bacillus subtilis wettable powder, subsequent field trials will be conducted to determine its potential as a microbial pesticide. This study provides important support for the future industrial production and application of the strain TCS001.